Respuesta :
Answer: x= 1 , y = 7
Step-by-step explanation:
y = -6x + 13 ................. equation 1
y = 3x + 4 ................ equation 2
substitute y = 3x + 4 into equation 1 , then we have
3x + 4 = - 6x + 13
collect the like terms , we have
3x + 6x = 13 - 4
9x = 9
x = 1
substitute x = 1 into equation 2 , we have
y = 3(1) + 4
y = 3 + 4
y = 7
Therefore : x = 1 and y = 7
Answer:
(1, 7 )
Step-by-step explanation:
Given the 2 equations
y = - 6x + 13 → (1)
y = 3x + 4 → (2)
Substitute y = 3x + 4 into (1)
3x + 4 = - 6x + 13 ( add 6x to both sides )
9x + 4 = 13 ( subtract 4 from both sides )
9x = 9 ( divide both sides by 9)
x = 1
Substitute x = 1 into (2) for corresponding value of y
y = 3(1) + 4 = 3 + 4 = 7
Solution is (1, 7 )